2014
DOI: 10.1097/aln.0000000000000070
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the Mandate for Hand-off Education

Abstract: The Accreditation Council for Graduate Medical Education requires that residency programs teach residents about handoffs and ensure their competence in this communication skill. Development of hand-off curricula for anesthesia residency programs is hindered by the paucity of evidence regarding how to conduct, teach, and evaluate handoffs in the various settings where anesthesia practitioners work. This narrative review draws from literature in anesthesia and other disciplines to provide recommendations for ane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 92 publications
(96 reference statements)
0
10
0
Order By: Relevance
“…Communications errors are estimated to account for 70% of preventable medical errors; half of which occur during patient handovers. 22, 23 Significant strides have been made to address this problem, most notably in post-operative handovers, where standardization and customization (i.e., to the unit and needs of the specific patient population) has resulted in increased provider satisfaction, improved teamwork and work efficiency, higher quality clinical communications, error reduction, and better patient outcomes. 4, 24 Preoperative handovers have been much less studied and published intervention studies with patient-specific outcomes are nearly non-existent.…”
Section: Discussionmentioning
confidence: 99%
“…Communications errors are estimated to account for 70% of preventable medical errors; half of which occur during patient handovers. 22, 23 Significant strides have been made to address this problem, most notably in post-operative handovers, where standardization and customization (i.e., to the unit and needs of the specific patient population) has resulted in increased provider satisfaction, improved teamwork and work efficiency, higher quality clinical communications, error reduction, and better patient outcomes. 4, 24 Preoperative handovers have been much less studied and published intervention studies with patient-specific outcomes are nearly non-existent.…”
Section: Discussionmentioning
confidence: 99%
“…Data have shown that these handoffs are times of significant risk to patients. 1 Specifically, studies have shown that handoffs from OR to postanesthesia care unit (PACU) and from OR to ICU often are laden with inaccuracies and miscommunication. 2,3 Three recent studies about handoffs and patient outcomes reported that there was a significant association between handovers and harm to patients.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies are difficult to interpret due to methodological bias stemming from the fact that the observations were not blinded. 813 In addition, the effect of handover protocols and checklists may be difficult to extrapolate to other countries, particularly when standardised communication is not yet a common part of everyday practice (currently the situation in France).…”
Section: Introductionmentioning
confidence: 99%